Theoretical Aspects of the Study of Pleonastic Expressions in Modern Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Pleonastic expressions represent an important object of study in modern linguistics, since they reflect the features of linguistic redundancy and its functional aspects. The article discusses theoretical approaches to the study of pleonastic expressions, their typology and functions in various language systems. Particular attention is paid to the analysis of their role in the formation of style and communicative effectiveness, as well as their impact on the perception of the text. The approach used includes both classical and modern linguistic theories, which allows us to identify the significance of pleonastic expressions in linguistic practice.